2022
DOI: 10.1093/nar/gkac1028
|View full text |Cite
|
Sign up to set email alerts
|

Selective degradation of tRNASer(AGY) is the primary driver for mitochondrial seryl-tRNA synthetase-related disease

Abstract: Mitochondrial translation is of high significance for cellular energy homeostasis. Aminoacyl-tRNA synthetases (aaRSs) are crucial translational components. Mitochondrial aaRS variants cause various human diseases. However, the pathogenesis of the vast majority of these diseases remains unknown. Here, we identified two novel SARS2 (encoding mitochondrial seryl-tRNA synthetase) variants that cause a multisystem disorder. c.654–14T > A mutation induced mRNA mis-splicing, generating a peptide insertion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…For example, a homozygous splicing variant in SARS2 that we identified in a patient who had early‐onset spastic paresis, led to a 95% reduction in the amount of SARS2 protein but had no apparent effect on mitochondrial protein synthesis in cultured skin fibroblasts 17 . SARS2 charges two different mitochondrial seryl‐tRNAs, and SARS2 mutations have been shown to selectively affect the stability of tRNA Ser AGY , which is an unusually small mitochondrial tRNA lacking the entire D domain 16,17,22 . The degree of tRNA instability varies between mutation and cell type.…”
Section: Mitochondrial Trna Charging Is Not Critical In Cultured Glyc...mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, a homozygous splicing variant in SARS2 that we identified in a patient who had early‐onset spastic paresis, led to a 95% reduction in the amount of SARS2 protein but had no apparent effect on mitochondrial protein synthesis in cultured skin fibroblasts 17 . SARS2 charges two different mitochondrial seryl‐tRNAs, and SARS2 mutations have been shown to selectively affect the stability of tRNA Ser AGY , which is an unusually small mitochondrial tRNA lacking the entire D domain 16,17,22 . The degree of tRNA instability varies between mutation and cell type.…”
Section: Mitochondrial Trna Charging Is Not Critical In Cultured Glyc...mentioning
confidence: 98%
“…Even if the mutation site was conserved in mice, obtaining a useful disease model can be challenging. It was recently reported that compound heterozygous SARS2 variants identified in a patient with a multisystem phenotype were both embryonic lethal as homozygotes in mice, as well as in compound heterozygosity, 22 suggesting species‐specific differences to tolerance of mitoARS defects.…”
Section: Challenges In Generation Of Mouse Models For Mitochondrial A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous expression of a Fars2 mutation (p.Asp142Tyr), which severely compromises mt-PheRS aminoacylation activity and causes hereditary spastic paraplegia in humans, is embryonically lethal in mice during early gestation, at a similar timepoint to Fars2 knockout mice ( Yang et al, 2016 ; Chen et al, 2022 ). Similarly, homozygous or compound heterozygous expression of human disease-causing Sars2 variants was embryonically lethal in mice ( Yu et al, 2022 ). The specific factors underlying the variation in phenotype severity between mouse and human carriers of isogenic ARS mutations are not known, however, these species differences should be considered when evaluating novel ARS disease models.…”
Section: Animal Model Systems For Studying Recessive Ars Diseasesmentioning
confidence: 99%
“…Another gene associated with an interesting spectrum of clinical phenotypes is mitochondrial seryl-tRNA synthetase ( SARS2 ). Patients with SARS2 variants present with (i) a progressive spastic paresis [ 53 ]; (ii) a syndrome characterized by hyperuricemia, pulmonary hypertension, renal failure in infancy, and alkalosis (HUPRA) that is typically lethal within the first few years of life [ 52 ]; or (iii) a syndrome that includes both neurological and HUPRA phenotypes [ 77 , 78 , 79 ]. Interestingly, HUPRA syndrome is exclusively associated with SARS2 , providing another example of unique mt-ARS phenotype.…”
Section: Clinical Heterogeneity Among Patients With Mutations In the ...mentioning
confidence: 99%